Diet Quality and Physical Activity and Their Association with BMI and Dental Caries Among High School Adolescents: A Cross-Sectional Study - Deema J. Farsi (Children)
Objectives: The aim of this study was to assess diet quality and its association with obesity and dental caries. It also assessed adolescents’ physical activity (PA) level and its relationship with obesity. Methods: This cross-sectional study examined 300 high school adolescents. Body mass indices (BMI) were calculated after taking participants’ heights and weights. Caries activity was recorded as decayed, missed, and filled scores (DMFT). Diet quality was assessed using the KIDMED questionnaire, and four additional questions were added to assess junk food consumption. PA was assessed using PAQ-A. KIDMED, junk food, and PA scores were calculated. Statistical analyses included Kruskal–Wallis and Wilcoxon Rank Sum tests for group comparisons. A Generalized Linear Model (GLM) was utilized to assess predictors of BMI percentile. Results: The KIDMED score was 3.0 ± 2.5, with 57.7% of participants classified as having very poor diet quality and 39% categorized as needing improvement. The majority of the participants had low PA levels (81.3%), with only 18% reporting moderate PA. No associations were observed between KIDMED scores, junk food consumption with BMI percentile, DMFT, or number of decayed teeth. Children with “very poor” KIDMED scores had a BMI percentile of 58.7 ± 33.9, while those with “needs improvement” and “optimal” diets had percentiles of 60.0 ± 30.0 and 65.1 ± 35.7, respectively. Higher PA levels were associated with better diet quality (p-value <0.001). The regression analysis, controlling for age, sex, DMFT, KIDMED, junk food consumption, and PA score did not identify any predictors of BMI percentile. Conclusions: Participants consumed poor quality diets and engaged in minimal PA. No associations could be concluded between diet and PA with either BMI or dental caries. Further research is needed to better understand these relationships.